Compatibility of Dicyma pulvinata with pesticides and biocontrol efficiency of South American leaf blight of rubber tree under field conditions - Melo, Débora Ferreira; Mello, Sueli Corrêa Marques de; Mattos, Carlos Raimundo Reis; Cardoso, Saulo Emilio Almeida (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate four isolates of the antagonist fungus Dicyma pulvinata in terms of its compatibility with chemical pesticides and adjuvants products, and the efficiency of these isolates as biocontrol agent against South American leaf blight (Microcyclus ulei) of rubber tree (Hevea sp.) under field conditions. Isolates compatibility with chemical pesticides and adjuvants was evaluated on mycelial growth and fungus sporulation in vitro. To assess the efficiency of the antagonist against M. ulei under field conditions, the four isolates were compared to the control by the fungicide mixture propiconazol + mancozeb. The assays showed incompatibility of the antagonistic fungus with the fungicides benomyl, carbendazim, mancozeb, propiconazol, besides the insecticide-acaricide endosulfan. Two of the adjuvants tested did not affect the fungus development. It was demonstrated the action of D. pulvinata against M. ulei, in the field, especially for the isolates CEN 62 and CEN 93, which showed control levels similar to the fungicide standard treatment.